2021
DOI: 10.1021/acs.biomac.0c01811
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine-Conjugated Glyconanoparticles for Chemo-photodynamic Combination Therapy

Abstract: Combination cancer therapy based on multifunctional nanomaterials has attracted great attention. The present work focuses on the preparation of the glycopolymeric nanoparticle, which contains a photosensitizer (zinc(II)phthalocyanine, ZnPc) and an anticancer drug (Doxorubicin, Dox). First, a novel mono azide-functional ZnPc-N 3 with seven hydrophilic ethylene oxide chains was synthesized. Next, ZnPc alone or together with Dox bearing glycopolymers was synthesized via the RAFT polymerization method and then sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 65 publications
0
38
0
Order By: Relevance
“…178,179 Some nanoparticles were even used in combination with chemotherapeutic strategies, with the anticancer drugs soranefib 180 and doxorubicin. 181 This dual photo-and chemotherapeutic strategy has also been implemented with molecular complexes, with a histone deacetylase inhibitor 182 or with immunotherapeutic activity. 183 We can also cite a recent work on ZnPcs that target tumours through PEG functionalization.…”
Section: Zincmentioning
confidence: 99%
“…178,179 Some nanoparticles were even used in combination with chemotherapeutic strategies, with the anticancer drugs soranefib 180 and doxorubicin. 181 This dual photo-and chemotherapeutic strategy has also been implemented with molecular complexes, with a histone deacetylase inhibitor 182 or with immunotherapeutic activity. 183 We can also cite a recent work on ZnPcs that target tumours through PEG functionalization.…”
Section: Zincmentioning
confidence: 99%
“…Polymeric micelles are fabricated rapidly from a large library of inexpensive starting materials and have tunable solubilization/dispersion properties to engineer in vivo performance. The properties of such micellar assemblies are strongly dependent on the architecture of their corresponding polymeric building blocks and, ultimately, the method employed in their synthesis. A variety of amphiphilic block copolymers with unique architectures have been investigated for drug delivery applications, including linear block copolymers and complex architectures such as brush and star-like polymers. …”
Section: Introductionmentioning
confidence: 99%
“…While the referenced cases demonstrate the potential photodynamic applications, the intrinsic photoactivity and tunability of phycobiliproteins, offered by their modular and flexible protein architecture, are overlooked and underutilized. Therefore, it is envisaged that with further development, the remarkable pH-responsiveness, photoactivity, and conformational flexibility of C-PC demonstrated in this work, along with this protein’s inherent biocompatibility and wide availability, will open new routes for its applications in cancer diagnosis, photodynamic therapy, drug delivery, and oxidation catalysis. Our future work will be directed toward a series of application-centered studies based on the identified tunability and photoactivity of C-PC. First, in vivo and in vitro tests will be conducted to assess the intracellular uptake, therapeutic efficacy, and tumor cell selectivity of C-PC under pH controls.…”
Section: Discussionmentioning
confidence: 96%